Student Satisfaction with Learning Facilities and Infrastructure PJOK SMP Muhammadiyah 3 Ampel - Muhammad Nafian Nurhuda; Gatot Jariono (UNIB Press, 2022)
Physical education aims to promote physical, mental, and emotional health. Facilities and infrastructure are needed to achieve the learning objectives of PJOK. That way the facilities and infrastructure can meet satisfaction with PJOK learning. There have been many studies conducted before regarding surveys of sports and health physical education learning facilities and infrastructure, but researchers want to examine the level of student satisfaction with sports and health physical education learning facilities and infrastructure that have not been researched much before. The purpose of this study was to see the level of student satisfaction with PJOK learning facilities and infrastructure at SMP Muhammadiyah 3 Ampel. Quantitative descriptive research method involving 60 students from all students at SMP Muhammadiyah 3 Ampel. Data collection techniques use questionnaires, observations, and documentation. Analyze the data using the help of Microsoft Excel. The results of the study obtained, that the level of student satisfaction with the PJOK learning facilities and infrastructure at SMP Muhammadiyah 3 Ampel was included in the category of